Effects of acetorphan, an enkephalinase inhibitor, on experimental and acute diarrhoea. Issue 6 (June 1992) - Baumer, P; Danquechin Dorval, E; Bertrand, J; Vetel, J M; Schwartz, J C; Lecomte, J M
Abstract : Acetorphan is an orally active inhibitor of enkephalinase (EC 3.4.24.11) with antidiarrhoeal activity in rodents apparently through protection of endogenous enkephalins and a purely antisecretory mechanism. Its antidiarrhoeal activity in man was assessed in an experimental model of cathartic induced secretory diarrhoea as well as in acute diarrhoea of presumed infectious origin. In six healthy volunteers receiving castor oil and pretreated with acetorphan or placebo in a crossover controlled trial, the drug significantly decreased the number and weight of stools passed during 24 hours. About 200 outpatients with severe acute diarrhoea (more than five stools per day) were included in a randomised double blind study of acetorphan against placebo. The significant antidiarrhoeal activity of acetorphan was established using a variety of criteria: (i) the duration of both diarrhoea and treatment were diminished; (ii) no acetorphan treated patient withdrew from the study whereas five dropped out because of worsening in the placebo group; (iii) the frequency of symptoms associated with diarrhoea–for example, abdominal pain or distension, nausea and anorexia–remaining after two weeks was nearly halved; (iv) using visual analogue scales acetorphan treatment was found more effective than placebo by both investigators and patients. There was statistically no significant difference between acetorphan and placebo in respect of side effects, particularly constipation, which often accompanies the antidiarrhoeal activity of mu opioid receptor agonists this difference is attributable to the lack of antipropulsive activity of acetorphan in man. The efficacy and tolerance of acetorphan suggest that enkephalinase inhibition may represent a novel therapeutic approach for the symptomatic management of acute secretory diarrhoea without impairing intestinal transit.